KẾT QUẢ BƯỚC ĐẦU NGHIÊN CỨU KHẢ NĂNG SINH TRƯỞNG VÀ PHÁT TRIỂN CỦA CÂY CHÙM NGÂY (Moringa Oleifera L.) TRỒNG TRÊN MỘT SỐ ĐẢO ĐÔNG BẮC VIỆT NAM - Lê, Xuân Đắc; Đặng, Hùng Cường; Trần, Thị Thanh Hương; Trần, Thị Nhàn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PRELIMINARY STUDIES ON THE DEVELOPMENT AND GROWTH OF Moringa oleifera L. IN NORTHEASTERN ISLANDS OF VIETNAM Moringa oleifera L. (Moringaceae) is a highly-valued plant distributed in the South and South Central of Vietnam. The results of this study show that the plants grow very well on the Northeastern islands (Co To and Tran islands): after two months of planting, survival rate of the plants is 82.0÷91.5% , plant height is 49.70÷53.70 cm, stem diameter is 1.78÷1.93 cm and number of leaves is 5.05÷6.10 leaves/tree. After 4 months, the plant height is 87.80÷90.10 cm, the stem diameter is 2.71÷2.87 cm and the number of leaves is 10.10÷10.30 leaves/tree. Fresh leaf yield after 6 months planting is 1.24÷1.51 kg/tree. The fresh leaves contain 91.82% water and 8.18% dry matter. The features reveal that the plants are able to grow normally in the ecological conditions of the islands.